2022
DOI: 10.1590/0103-6440202204990
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to lipopolysaccharide and calcium silicate-based materials affects the behavior of dental pulp cells

Abstract: This study assessed the cell viability, cytokine production, and mineralization potential of human dental pulp cells (hDPCs) after exposure to lipopolysaccharide (LPS) and application of calcium silicate-based materials (CSBM). Characterization of the CSBM was performed by infrared spectroscopy (n = 3). Extracts of Bio-C Repair, Biodentine, Cimmo HD, and MTA Repair HP were prepared and diluted (1:1, 1:4, and 1:16). Culture of hDPCs was established and treated or not with 1 µg/mL of LPS from Escherichia coli fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Another approach explored involves analyzing the behavior of DPSCs in interaction with bioactive materials to develop strategies in pulp therapy. Pedroza et al ( 2022) reported that creating an inflammatory environment (1 µg/mL of LPS) in DPSCs using calcium silicate-based materials improved proliferation and mineralization potential while inducing anti-inflammatory mechanisms [64].…”
Section: Effect Of Bacterial Lps On the Biological Characteristics Of...mentioning
confidence: 99%
“…Another approach explored involves analyzing the behavior of DPSCs in interaction with bioactive materials to develop strategies in pulp therapy. Pedroza et al ( 2022) reported that creating an inflammatory environment (1 µg/mL of LPS) in DPSCs using calcium silicate-based materials improved proliferation and mineralization potential while inducing anti-inflammatory mechanisms [64].…”
Section: Effect Of Bacterial Lps On the Biological Characteristics Of...mentioning
confidence: 99%
“…P. gingivalis, its LPSs, or the inflammatory cytokines induced by this bacterium affect the differentiative potential, but not the survival or growth, of DPSCs [118,119,127]. In contrast, the LPSs of Escherichia coli, another bacterium involved in periodontitis [181], increase DPSCs viability [182], possibly favoring endodontic carcinogenesis.…”
Section: Endodontic Infections By P Gingivalis or F Nucleatum And End...mentioning
confidence: 99%